HubunganKecerdasanEmosionalDenganStres Akademik MahasiswaKeperawatan - Cahyaningsih, Ayu Marlina; Cahyaningtyas, Anindhita Yudha; Wulandari, Dewi (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2024)
High emotional intelligence makes a person able to control emotions and manage stress. Good emotional intelligence is needed by students, especially in dealing with academic stress that they may experience. This research is to determine the relationship between emotional intelligence and academic stress. This research design uses an analytical observational study with quantitative data collection through a cross-sectional approach. The population in this study were nursing students, with a total sample of 111 respondents with technique proportionate stratified random sampling. Data analysis used univariate analysis with frequency distribution and the Spearman Rho test. Analysis of univariate results showed that some respondents had moderate emotional intelligence (83.8%) and experienced moderate academic stress (82.9%). The results of the research showed that there was a relationship between emotional intelligence and academic stress for nursing students, obtained p < 0.001.